2002
DOI: 10.1046/j.1472-765x.2002.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of oil-degrading microorganisms from lubricating oil contaminated (scale) soil

Abstract: Aims: To isolate and characterize oil‐degrading microorganisms from contaminated (scale) soil. 
Methods and Results: Oil‐degrading microorganisms were isolated from enrichment cultures of scale soil. Each isolate was identified using 16S rDNA gene and oil degradability was determined on both unused and used lubricating oil. The weight of the extracted remaining oil revealed that most isolates degraded unused lubricating oil more than used lubricating oil. Chemical composition of oil analysed by TLC‐FID and GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…Leahy and Cowell (1990), demonstrated that microorganisms were the main degraders of petroleum hydrocarbons in contaminated ecosystems. Enrichments to isolate oil-degraders using diesel as sole carbon and energy source have generated various microorganisms from several genera (Jirasripongpun 2002). In the present study, six bacterial species namely S 1 P 1 , S 3 P 3 , S 2 P 2 , S 2 P 1 , S 3 P 2 with potentials in degradation of diesel were isolated.…”
Section: Resultsmentioning
confidence: 92%
“…Leahy and Cowell (1990), demonstrated that microorganisms were the main degraders of petroleum hydrocarbons in contaminated ecosystems. Enrichments to isolate oil-degraders using diesel as sole carbon and energy source have generated various microorganisms from several genera (Jirasripongpun 2002). In the present study, six bacterial species namely S 1 P 1 , S 3 P 3 , S 2 P 2 , S 2 P 1 , S 3 P 2 with potentials in degradation of diesel were isolated.…”
Section: Resultsmentioning
confidence: 92%
“…Growth of the isolates was estimated by cell dry weight, as well as by total soluble cell protein measurement as described by Feitkenhauer et al (2003). At the same time, % oil degradability in each culture was calculated as described by Jirasripongpun (2002).…”
Section: Synthesis Of Bacterial Consortiamentioning
confidence: 99%
“…Pseudomonas may play an important role in coal solubilization as many pseudomonads have been reported to produce a variety of rhamnolipids— surface-active agents (surfactants) with the ability to solubilize hydrophobic carbon sources 41–43 . Production of rhamnolipids is controlled by many factors, including temperature, salinity, pH, and nutrient availability 43,44 and may be induced by coal or coal substituents 42 . Both Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 99%